Behavioral, emotional, and situational context of purging episodes in anorexia nervosa. Issue 3 (27th January 2015) - Goldschmidt, Andrea B.; Accurso, Erin C.; Schreiber‐Gregory, Deanna N.; Crosby, Ross D.; Cao, Li; Engel, Scott G.; Mitchell, James E.; Crow, Scott J.; Peterson, Carol B.; Le Grange, Daniel; Wonderlich, Stephen A.
ABSTRACT: Objective: The current study examined behavioral, emotional, and situational factors involved in purging among women with anorexia nervosa (AN). Method: Women with AN ( n =118) completed a two‐week ecological momentary assessment protocol involving daily reports of eating disorder behaviors, mood, and stressful events. Generalized estimating equations examined the likelihood and context of purging following eating episodes involving both overeating and loss of control (binge eating; BE); loss of control only (LOC); overeating only (OE); and neither loss of control nor overeating (non‐pathological eating; NE). Results: Relative to NE, purging was more likely to occur following BE, LOC, and OE (Wald chi‐square = 18.05; p  < .001). BE was more strongly associated with subsequent purging than LOC but not OE; the latter two did not differ from one another. Negative affect predicted purging following NE (Wald chi‐square = 7.71; p  = .005). Discussion: Binge eating involving large amounts of food was the strongest predictor of purging in AN, which challenges the notion that loss of control is the most salient aspect of experiencing distress in bulimia nervosa and BE disorder. Parallel to findings from the BE literature, negative affect strongly predicted purging following NE. Further research should clarify the function and triggers of purging in AN. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:341–344)